Analisis Hukum dan Ekonomi Prinsip Murabahah dalam Transaksi Perbankan Syariah - Ayu Sukreni Hakim; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This article delves into the intricacies of the murabahah principle within the realm of Islamic banking, examining it from both legal and economic standpoints. Murabahah is a unique form of sale and purchase transaction where an Islamic bank procures goods requested by a customer and resells them at a predetermined price encompassing the original cost and an agreed-upon profit margin. The foundation of this principle rests upon ensuring fairness and transparency in transactions while adhering to Sharia principles that prohibit usury (riba). This research meticulously explores the relevance of murabahah in the context of Islamic banking, the resulting economic implications, and the controversies that arise surrounding its implementation. The findings of the analysis reveal that murabahah not only presents an Islamically compliant financing alternative but also fosters financial inclusion and sustainable economic development.